Using Electromagnetics to Map Lateral Fluid Variations in Carbonates in SE Asia - Strack, K.; Davydycheva, S. (New Approaches in Engineering Research Vol. 2, 2021)
Exploration for hydrocarbon is often difficult when the overlaying strata is of high seismic velocity as it is for basalt, salt and carbonates. Many the world reservoirs are in carbonates. Mapping the reservoir laterally is thus difficult and developing carbonate reservoirs is expensive. We propose to use controlled source electromagnetic (CSEM) method to image the fluid better. In SE Asia commonly magnetotellurics, a passive method, is being used [1], but they are less sensitive to deep subsurface resistivity variations as CSEM. Pioneering work with CSEM was done in the 1980s in Australia and Europe [2] where CSEM was used to map resistive reservoirs / carbonates. Since then, the equipment and modeling methods have significantly improved, and the problem is addressed more cost effective thus reducing exploration cost by several fold. Applying a new differential measurement methodology and using 3-dimensioanal (3D) anisotropic model derived from well logs and 3D modeling we are able remove near surface anomalies and illuminate the deep the reservoir target and its lateral variations. Thus, we have a cost-effective solution for many exploration and production problems associated with carbonates.